2019
DOI: 10.11113/jt.v81.13670
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentration of Bisphenol a Induces Proliferation of Gastric Cancer Cells, HGC-27

Abstract: Bisphenol A, an endocrine disrupting compounds that affect human homeostasis. Studies on BPA are focusing on the impact of BPA in reproductive function and brain development. However, the effect of BPA on gut especially gastric cells is not well explored. Gut is directly in contact with ingested BPA; therefore, we aimed to determine the effect of BPA exposure on gastric cells proliferation at safe recommended concentration. Human gastric cancer cells (HGC-27) were treated with BPA at different concentration (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the same protein, an increased z-score from −3.23 to −1.19 was noted, whereas for the mutant-type protein, the z-score changed from −3.24 to −1. 16.…”
Section: Landscape Of Mutations In Seven Biomarker Genes Based On Tcg...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same protein, an increased z-score from −3.23 to −1.19 was noted, whereas for the mutant-type protein, the z-score changed from −3.24 to −1. 16.…”
Section: Landscape Of Mutations In Seven Biomarker Genes Based On Tcg...mentioning
confidence: 99%
“…Bisphenol A (BPA) (an EDC) has a pro-carcinogenic impact in hormone-dependent and hormone-independent cancers [9][10][11]. BPA exposure is reported to alter the cancer cells' biological behaviours, particularly, proliferation, invasion, growth, survival, migration and apoptosis [9,[12][13][14][15][16]. Recently, we have identified seven genes that have prognostic power for the overall survival in OC, namely Guanylate Binding Protein 5 (GBP5), Insulin Receptor Substrate 2 (IRS2), Keratin 4 (KRT4), long intergenic non-protein coding RNA 707 (LINC00707), Mitochondrial Ribosomal Protein L55 (MRPL55), Ribosome Biogenesis Regulator 1 Homolog (RRS1) and Solute Carrier Family 4 Member 11 (SLC4A11).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that BPA exposure has a pro-carcinogenic influence in hormone-dependent and hormone-independent cancers (Gao et al 2015 ; Seachrist et al 2016 ). BPA exposure is reported to alter the cancer cells’ biological behaviors, notably, proliferation, invasion, growth, survival, migration, and apoptosis (Chevalier et al 2012 ; Prins et al 2014 ; Ge et al 2014 ; Wang et al 2015 , 2017 , 2019 ; Ma et al 2015 ; Song et al 2015 ; Pfeifer et al 2015 ; Shi et al 2017 ; Jeong et al 2017 ; Sauer et al 2017 ; Li et al 2017 ; Huang et al 2018 ; Hui et al 2018 ; Qu et al 2018 ; Hanafi et al 2019 ). Besides, in vitro studies have shown that low doses of BPA exposure have reported inducing resistance to anticancer drugs such as tamoxifen (TAM), carboplatin, poly ADP ribose polymerase (PARP) inhibitors, doxorubicin, bevacizumab, vinblastine, cisplatin, and others by modulating the expression of many oncogenic signaling pathways in both hormone-dependent and hormone-independent human cancers (Hafezi and Abdel-Rahman 2019 ).…”
Section: Introductionmentioning
confidence: 99%